Glucagon-like peptide 1 (GLP-1) receptor agonists in experimental Alzheimer’s disease models: a systematic review and meta-analysis of preclinical studies - Kong, Fanjing; Wu, Tianyu; Dai, Jingyi; Zhai, Zhenwei; Cai, Jie; Zhu, Zhishan; Xu, Ying; Sun, Tao (Frontiers in Pharmacology, 2023)
Alzheimer's disease (AD) is a degenerative disease of the nervous system. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs), a drug used to treat type 2 diabetes, have been shown to have neuroprotective effects. This systematic review and meta-analysis evaluated the effects and potential mechanisms of GLP-1 RAs in AD animal models. 26 studies were included by searching relevant studies from 7 databases according to a predefined search strategy and inclusion criteria. Methodological quality was assessed using SYRCLE's risk of bias tool, and statistical analysis was performed using ReviewManger 5.3. The results showed that, in terms of behavioral tests, GLP-1 RAs could improve the learning and memory abilities of AD rodents; in terms of pathology, GLP-1 RAs could reduce Aβ deposition and phosphorylated tau levels in the brains of AD rodents. The therapeutic potential of GLP-1 RAs in AD involves a range of mechanisms that work synergistically to enhance the alleviation of various pathological manifestations associated with the condition. A total of five clinical trials were retrieved from ClinicalTrials.gov. More large-scale and high-quality preclinical trials should be conducted to more accurately assess the therapeutic effects of GLP-1 RAs on AD.